2009
DOI: 10.1073/pnas.0907402106
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electrophoretic response yields a unique parameter for separation of biomolecules

Abstract: We demonstrate a unique parameter for biomolecule separation that results from the nonlinear response of long, charged polymers to electrophoretic fields and apply it to extraction and concentration of nucleic acids from samples that perform poorly under conventional methods. Our method is based on superposition of synchronous, time-varying electrophoretic fields, which can generate net drift of charged molecules even when the time-averaged molecule displacement generated by each field individually is zero. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…It should also be noted that SCODA is fundamentally different from other electrophoretic separation www.cshprotocols.org 3 Cold Spring Harbor Protocols and sample preparation techniques (such as PFGE) because SCODA can concentrate all DNA molecules above ~300 bp into a buffer sample while simultaneously removing contaminants. Other electrophoretic mechanisms are unable to concentrate samples, and also do not provide a method for effective contaminant removal (Pel et al 2009). This protocol highlights SCODA's strengths as a general method for recovering small amounts of DNA from contaminated samples (Broemeling et al 2008;Pel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that SCODA is fundamentally different from other electrophoretic separation www.cshprotocols.org 3 Cold Spring Harbor Protocols and sample preparation techniques (such as PFGE) because SCODA can concentrate all DNA molecules above ~300 bp into a buffer sample while simultaneously removing contaminants. Other electrophoretic mechanisms are unable to concentrate samples, and also do not provide a method for effective contaminant removal (Pel et al 2009). This protocol highlights SCODA's strengths as a general method for recovering small amounts of DNA from contaminated samples (Broemeling et al 2008;Pel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is based on methods described in Broemeling et al (2008), Marziali et al (2005), and Pel et al (2009). iii.…”
Section: Related Informationmentioning
confidence: 99%
“…A recent report has indicated that an automated, magnetic bead based, DNA extraction system can improve the sensitivity (over the silica column approach) of a real-time PCR based method to detect bacteria associated with sepsis in blood samples [20]. Such an approach, or other methods where DNA is processed from larger sample volumes [21,22], could well increase the amount of agent DNA presented to each assay, and help increase the sensitivity of B. anthracis PCRs. This would also help bridge the gap in sensitivity between blood culture and PCR and allow the best chance of a rapid diagnosis, without a requirement for extended incubation periods.…”
Section: Discussionmentioning
confidence: 99%
“…In prior works, it was found that transient flow depends on the transverse size of the channel and may provide some unique property. For instance, pulsed DC electric fields can enhance separation based on electrophoresis (Frumin et al 2001;Lin et al 2008;Pel et al 2009) and the fidelity of the pulse, which is related to the rise time of electroosmotic flow (EOF), can affect the separation efficiency (Heiger et al 1992). AC EK is an intrinsically unsteady process, so are the initial phase of EOF and sample injection, etc.…”
Section: Introductionmentioning
confidence: 99%